Alleviation of Toxicity Caused by Overactivation of Pparα through Pparα-Inducible miR-181a2 - Yanjie Cheng; Zhuying Wei; Shengsong Xie; You Peng; Yi Yan; Dan Qin; Shenghui Liu; Yanling Xu; Guangpeng Li; Lisheng Zhang (Elsevier, 2017)
Widely varied compounds, including certain plasticizers, hypolipidemic drugs (e.g., ciprofibrate, fenofibrate, WY-14643, and clofibrate), agrochemicals, and environmental pollutants, are peroxisome proliferators (PPs). Appropriate dose of PPs causes a moderate increase in the number and size of peroxisomes and the expression of genes encoding peroxisomal lipid-metabolizing enzymes. However, high-dose PPs cause varied harmful effects. Chronic administration of PPs to mice and rats results in hepatomegaly and ultimately carcinogenesis. Nuclear receptor protein peroxisome proliferator-activated receptor-α (Pparα) was shown to be required for this process. However, biological adaptations to minimize this risk are poorly understood. In this study, we found that miR-181a2 expression was induced by the Pparα agonist WY-14643. Moreover, exogenous expression of miR-181a-5p dramatically alleviated the cell toxicity caused by overactivation of Pparα. Further studies showed that miR-181a-5p directly targeted the Pparα 3' untranslated region and depressed the Pparα protein level. This study identified a feedback loop between miR-181a-5p and Pparα, which allows biological systems to approach a balance when Pparα is overactivated.